2021
DOI: 10.1152/ajpheart.00934.2020
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the thread of uncontrolled immune response in COVID-19 and STEMI: an emerging need for knowledge sharing

Abstract: The outbreak of severe acute respiratory syndrome coronavirus 2 that first emerged in Wuhan in December 2019 has resulted in the devastating pandemic of coronavirus disease 2019, creating an emerging need for knowledge sharing. Meanwhile, myocardial infarction is and will probably remain the foremost cause of death in the western world throughout the coming decades. Severe deregulation of the immune system can unnecessarily expand the inflammatory response and participate in target and multiple organ failure, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 108 publications
(243 reference statements)
0
1
0
Order By: Relevance
“…Uncontrolled inflammatory responses are closely associated with poorer outcomes in COVID-19 [49][50][51][52][53][54] . Tregs are often responsible for restraining excessive immune responses, and previous work has found that Treg frequencies were increased in severe COVID-19 patients 55 .…”
Section: Comparative Immune Cell Analyses Of Non-pregnant Versus Preg...mentioning
confidence: 99%
“…Uncontrolled inflammatory responses are closely associated with poorer outcomes in COVID-19 [49][50][51][52][53][54] . Tregs are often responsible for restraining excessive immune responses, and previous work has found that Treg frequencies were increased in severe COVID-19 patients 55 .…”
Section: Comparative Immune Cell Analyses Of Non-pregnant Versus Preg...mentioning
confidence: 99%